Anarchy Is What Explains the History of International Relations - William C. Wohlforth (Vestnik MGIMO-Universiteta)
The article examines the major events of the two previous centuries of international relations through main concepts of political realism. The author argues that in order to understand the present dilemmas and challenges of international politics, we need to know the past. Every current major global problem has historical antecedents. History from the late 19th century constitutes the empirical foundation of much theoretical scholarship on international politics. The breakdown of the Concert of Europe and the outbreak of the devastating global conflagration of World War I are the events that sparked the modern study of international relations. The great war of 1914 to 1918 underlined the tragic wastefulness of the institution of war. It caused scholars to confront one of the most enduring puzzles of the study of international relations, why humans continue to resort to this self-destructive method of conflict resolution? The article shows that the main explanation is the anarchical system of international relations. It produces security dilemma, incentives to free ride and uncertainty of intentions among great powers making war a rational tool to secure their national interests.This research is funded by the Ministry of Science and Higher Education of the Russian Federation (grant agreement number 14.461.31.0002).